Effect of Disinfection on Some Properties of Heat-Vulcanized Maxillofacial Silicone Elastomer Reinforced by Nano Silicone Dioxide - Fouad, Madiha; Moudhaffer, Mohammed (Journal of Baghdad College of Dentistry, 2016)
Background: The daily cleaning routine of the silicone maxillofacial prostheses by the patient may cause some alteration in the materials properties. The purpose of the present study was to investigate the effect of different disinfection procedures on some properties of silicon dioxide reinforced Cosmesil M511 HTV maxillofacial silicone.Materials and Methods: One hundred and sixty (160) specimens were prepared by mixing 5% SiO2 nano particles and 0.5% intrinsic cream color into the silicone polymer according to manufacturer's instructions. Specimens were divided into 4 groups according to the performed test (tear strength, surface hardness, surface roughness and color) with 40 specimens each. Each group was further subdivided according to the disinfection procedure conducted (control, microwave exposure, neutral soap and 4% chlorhexidine gluconate). Measurements for tear strength were done using universal testing machine. Surface hardness test was carried out with a Shore A Durometer. Surface roughness was analyzed with a portable digital Profilometer. Color change was established with a Spectrophotometer. After the initial testing, all specimens were submitted to disinfection procedure 3 times a week for 60 days. Measurements were repeated and data were statistically analyzed using one-way ANOVA followed by Fisher's LSD or Games-Howell test. Results: Spectrophotometer results showed non-significant decrease in the light absorbance of all experimental groups after disinfection, indicating a strong integration between the nano filler and the polymeric chains, which was not broken during the disinfection procedure. Highly-significant increase in Shore A hardness was recorded, while the decrease in surface roughness was highly significant in all experimental groups. Tear strength reduced significantly after disinfection in all experimental groups.Conclusion: Disinfection seemed to cause different amount of alteration in all of the tested properties of silicone. High color stability is expected in this type of maxillofacial silicone after disinfection.Although microwave exposure had increased the hardness of the material, it is considered a satisfactory disinfection procedure since it caused the least effect on the tear strength and surface roughness of the material. Therefore, microwave exposure is recommended for the disinfection of maxillofacial silicone prostheses.